FROM PROBLEM TO SOLUTION: THE ROLE OF FADEYI, MUSHIN AND OJUELEGBA AREA BOYS IN LAGOS’ COVID-19 LOCKDOWN INSECURITY (Glocalism: Journal of Culture, Politics and Innovation, 2025)
The history of pandemic outbreaks is replete with disruptions that resonate beyond the immediate realm of health and wellness. The outbreak of COVID-19 triggered unprecedented consequences across the world. In parts of Lagos, Nigeria’s commercial capital, compulsorily enforced lockdown, alongside the void created by inadequate policing, caused widespread insecurity and crimes linked to so-called “one million boys”. Traditionally, the menace of area boyism is rife in Lagos and extant literature has focused on the groups’ acrimonious history of violence, extortion and crime. This paper examines the nexus between COVID-19 lockdown, rampant insecurity and area boys’ interventions in Fadeyi, Mushin and Ojuelegba areas of Lagos. It argues that, despite their flawed reputation, area boys became instrumental in residents’ search for an unconventional solution to rising crime rates in Lagos in line with the popular Yoruba saying: “Olè ló mọ ẹsẹ̀ olè tọ̀” (it is a thief that knows how to catch another thief). The study draws from a number of sources – archival materials, in-depth fieldwork, and secondary materials and adopts the qualitative and descriptive research method. Its finding indicates that COVID-19 lockdown in Lagos State did not only stimulate widespread insecurity and criminal activities, but also prompted unconventional security intervention from the most unlikely sources. It concludes that the sheer degree of energy currently being misapplied by area boys can be harnessed to further the course of national development in several crucial areas.
Keywords: area boys; awawa boys; COVID-19; Lagos; one million boys